Demographic Features and The Factors Influencing ‎Investment in Mutual Funds: Evidence from Kamrup ‎Metro District - Debnath, Dr. Jasojit; Belho, Dr. Vizosanuo (International Journal of Accounting and Economics Studies, 2026)
Mutual funds offer investors the opportunity to invest in diversified schemes based on their ‎risk appetite. Various factors influence investors’ decisions, which stem from their demographic ‎and socio-economic characteristics. This study investigates the demographic features and factors ‎influencing mutual fund investments and examines the relationship between them. Primary data ‎were collected from 350 randomly selected residents of the Kamrup Metro district in the state of Assam, India, for drawing ‎conclusions. High returns, portfolio diversification, and tax benefits are the most critical factors ‎influencing mutual fund investment decisions. Significant differences were observed among ‎investors based on gender, marital status, and educational qualification‎.